Organisational Baseline Study: Overview report for Ma CSV, Vietnam (VN01) - Hieu, Do Trong; San, Le Viet; Hoan, Le Khai; Quyen, LN; Sen, P.T. (2015)
According to the data provided by Yen Bai Statistics Department (YSD), the total area of Yen Bai about 668,628 ha, of which 87.5% (585,089 ha) are agricultural land. Most of the province’s agricultural lands are sloping. The province shares the common features of the North-western Vietnam: terrain is complicated and are strongly fragmented by mountain and stream systems; climate is tropical and with different climatic sub- regions. Over 70% of the population (over 70%) are agricultural. Yen Binh district locates in the south of Yen Bai province, with the total area of 77,262 ha, and is diverse and rich in natural resources. Having diverse agricultural production activities (including crop, livestock, aquaculture and forestry) and sharing the common features with the province, Ma village has been facing important challenges caused by natural resource degradation, environmental pollution and climate variability. On the other hand, there are also great potentials for this village to develop sustainable and climate smart livelihoods and agriculture. Ma village, Vinh Kien commune, Yen Binh district, Yen Bai province has therefore been selected to be a site for building Climate Smart Villages (CSV) under the CGIAR Program “Climate Change, Agriculture and Food Security (CCAFS). An organization baseline survey, was therefore conducted as part of the baseline effort for this village, which consists of three components – household survey, village study and organizational survey. The objectives of this organization baseline study (OBS) include: - Provide indicators to allow us to monitor changes in behaviours and practices of relevant local organizations over time; - Understand the current status of provision of information/services at the local level that informs farmers’ decision making about their livelihood strategies in response to climate change. To gather necessary information, we conducted survey of organizations of which activities covered a wide range in all the aspects: natural resources management, environment and climate change, agricultural production, agricultural product processing and input supplying. The list of these organization is presented in Table 1.